Balay Mangi an integrated post harvesting and processing hub design for corn industry through exploratory application of lean six sigma DMAIC as an architectural design method - Recto, Charles Eiron T.; David Xander T. Lacson (Quezon City College of Architecture, University of the Philippines Diliman, 2025)
The substantial production of corn in the country signifies its essentiality to Filipino sustenance. Despite being a vital industry, the agricultural landscape of the country lags behind in the availability of sufficient facilities for post harvesting and processing. This has pushed small-scale farmers (SSFs) to practice traditional farming methods in informal spaces, thereby compromising efficiency. The current supply chain in the corn industry also shows that SSFs only engage until the post-harvesting stage, excluding them from exploring the economic opportunities in processing. This study explored the integration of post-harvesting and processing of corn in a facility that will streamline the opportunities for SSFs. Considering systemic efficiency at the forefront of the design, the Lean Six Sigma DMAIC methodology was utilized to identify sources of waste and inefficiency in current practices, serving as a guide in applying relevant processes and spaces only within the typology. The site of the facility shall be built in the rural town of Tumauini, Isabela, within the vicinity of ten barangays with the largest size of corn farmland in the municipality. Considering the farming cycle of corn, the exploration of a retractable post harvesting unit was done to ensure that the space will adapt to user needs even during off-harvest season, backed up by an appropriate mechanism to operate. Providing systemic flow in the spatial organization of spaces in the processing hub also secured efficiency and safety in food production. Thus, this research aims to introduce a paradigm shift in the corn industry by providing the SSFs a facility to explore their opportunity to engage in more value-adding processes that will lessen their time spent in post harvesting while including them in the processing stage.
Include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Corn -- Processing; Six sigma (Quality control standard); DMAIC; Architectural design -- Isabela